Behavior of CBR value of laterite soil mixed with metakaolin - Setiawan, Dedy; Rusdiansyah, Rusdiansyah (Technium: Romanian Journal of Applied Sciences and Technology, 2024)
Laterite soil is a material widely used for civil engineering purposes in South Kalimantan. Most laterite soil has low bearing capacity due to high clay and plastic content, causing cracks and damage, especially when mixed with a fairly high volume of water. Therefore, this study aimed to improve the soil through stabilization using metakaolin. An experimental study was conducted using laterite soil from Mount Kupang, Cempaka Village, Banjarbaru. This soil wasmixed with metakaolin on various percentage variations of the mixture, namely 2%, 4%, 6%, 8%, and 10% of the weight. The incubation period of the sample commences from 3, 7, and 14 days. Some of the test conducted include soil consistency limits (Atterberg limit test), soaked laboratory, and unconfined compressive strength (UCT). The result showed an effect on the characteristics of laterite soil mixed with metakaolin. The Plasticity Index (PI) value of laterite soil experienced a constant decrease due to the influence of methakoline by 14.75%. The soaked CBR value increased in a mixture of 2 to 8% metakaolin, but there was a decrease in the case of 10% at a curing time of 3, 7, and 14 days. Furthermore, the maximum soaked CBR value in laterite soil samples was mixed with 10% metakaolin at a curing period of 14 days and experience a percentage increase of 43.47%. The maximum qu value also increased by 42.02% in a mixture of 8% metakaolin and decreased in a 10% metakaolin at a curing time of 14 days.